Efficacy of Routine Magnetic Resonance Imaging (MRI) in Evaluation of Knee Joint Pathologies - Adil Ali Khan; Rastogi, Rajul; Pratap, Vijai; Pathak, Satish; Pant, Ajay; Gupta, Yuktika; Mittal, Vishakha; Goel, Sarika (Asian Journal of Medical Radiological Research, 2020)
Background: Imaging modalities like ultrasonography (USG), magnetic resonance imaging (MRI) and magnetic resonance arthrography (MRAr) provide different form of information about the joint space and tendons related to the knee joint. Knee is the most frequently examined joint by MRI / MRAr as it is relatively non-invasive and highly accurate in assessing joint structures, saving majority of patients from non-therapeutic arthroscopy procedures. The main objective of this study is to understand the comparative role of routine MRI and MRAr in our hospital settings. Subjects and Methods: Twenty-five patients included in the study underwent both MRI and MRAr on the same day. Results were interpreted by radiologists and data was tabulated with the final diagnosis established on MRAr. Results: Efficacy of MRI was inferior in evaluation of Anterior Cruciate ligament, meniscal and capsular tears. In patients, where MRI was normal, MR Arthrography revealed significant findings. Conclusion: Routine MRI misses significant outcome information when compared to MRAr in evaluation of knee joint. Hence, MR Arthrography should be done for optimal evaluation of knee joints in all patients especially those with clinicoradiological discordance.